Decoding Corona Conscience: Analysis from the Lens of Power Posture, Vedic Philosophy and Hindu Civilization with Reference to Nepal - Dahal, Atindra (Europasian Journal of Medical Sciences, 2020)
Background: The world, though completely unwillingly, has been surfing with the most severely heart-rending and probably the highest form of suffering of the century called CoronaVirus (COVID-19). On very outset, this paper tries to trace a few remarkable messages that the world has to infallibly and flawlessly deduce, decode and assimilate over Corona from non-pharmaceutical, non-medical and non-military vantage points. It tries unfolding the grandeur of ‘Vedic philosophy and Hindu civilization based rural life practice’ in mitigating such pandemic-induced health hazards. It even assesses pros and cons of Corona in Nepal. Method: This paper has adopted doctrinal and archival methodology. Researcher’s argument is derived through the paradigm of interpretation, analogy, by juxtaposing situations, and taking references of perceptions and views expressed by various scholars, duly cited with acknowledgment. A variety of relevant and recently published works i.e. major books, pertinent articles, and frequently viewed and cited sources found in Google Scholar, SCOPUS, MedLine, academia.edu are cited considering the gravity and validity of needed content. Their insight and intuition are used to support as premise while reasoning arguments. Result: Eventually, following propositions are drawn that: pandemic is a recurring evil; it has seriously challenged the existing notion of world power strength; it has justified that behaviors based on Vedic philosophy and Hindu civilizations are prone and proficient to prevent such infections. Besides, Corona can herald both positive and negative outcomes to Nepal, ahead. Conclusion: This paper recommends that now all concerned authorities should delve and devise on preventing such plagues and pandemics through modifications on living manner (being aligned with Vedic Philosophy and Hindu Civilization) than being overhyped on medicines/vaccines. Power should be understood in a new way; Nepal ought not to be much pessimist in light of economic future.